2023
DOI: 10.3389/fspas.2023.989443
|View full text |Cite
|
Sign up to set email alerts
|

MORPHOFIT: An automated galaxy structural parameters fitting package

Abstract: In today’s modern wide-field galaxy surveys, there is the necessity for parametric surface brightness decomposition codes characterised by accuracy, small degree of user intervention, and high degree of parallelisation. We try to address this necessity by introducing MORPHOFIT, a highly parallelisable python package for the estimate of galaxy structural parameters. The package makes use of wide-spread and reliable codes, namely, SEXTRACTOR and GALFIT. It has been optimised and tested in both low-density and cr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
10
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(11 citation statements)
references
References 63 publications
1
10
0
Order By: Relevance
“…The AS1063 and M1149 spectroscopically confirmed cluster members we use in our analysis are the same as those selected in Tortorelli et al 2018 using VLT/MUSE IFU spectra. They are 95 for AS1063, having redshifts in the range 0.335 ≤ z ≤ 0.361 (Karman et al 2015), and 68 with redshifts 0.52 ≤ z ≤ 0.57 (Grillo et al 2016) for M1149.…”
Section: Datasetmentioning
confidence: 99%
See 4 more Smart Citations
“…The AS1063 and M1149 spectroscopically confirmed cluster members we use in our analysis are the same as those selected in Tortorelli et al 2018 using VLT/MUSE IFU spectra. They are 95 for AS1063, having redshifts in the range 0.335 ≤ z ≤ 0.361 (Karman et al 2015), and 68 with redshifts 0.52 ≤ z ≤ 0.57 (Grillo et al 2016) for M1149.…”
Section: Datasetmentioning
confidence: 99%
“…They are 119 with redshifts 0.38 ≤ z ≤ 0.41. The description of the member selection is detailed in Annunziatella et al 2017 andCaminha et al 2017. In Tortorelli et al 2018, we defined and compared four different galaxy samples according to (a) Sérsic indices: early-type ('ETG'), (b) visual inspection: 'ellipticals', (c) colours: 'red', (d) spectral properties: 'passive'. We showed that the KR built with the 'ETG' sample is fully consistent with the ones obtained with the 'elliptical' and 'passive' samples.…”
Section: Datasetmentioning
confidence: 99%
See 3 more Smart Citations